Estimation of matrix metalloproteinase‑3 levels in gingival crevicular fluid in periodontal disease, health and after scaling and root planing - N Ravindra Reddy; D Roopa; D S Madhu Babu; P Mohan Kumar; C Mahendra Raju; N Sarath Kumar (Wolters Kluwer Medknow Publications, 2012)
Background: Initial research has shown a positive correlation between the severity of periodontal disease and matrix metalloproteinase-3 (MMP-3) concentrations in gingival crevicular fluid (GCF). However, there are no enough reports to correlate the MMP-3 concentrations in GCF in periodontal health, disease and after treatment. Hence, the present study is to estimate the levels of MMP-3 in GCF in periodontal health, disease and to evaluate the effect of periodontal therapy on MMP-3 concentrations in GCF. Materials and Methods: Periodontal examination and collection of GCF by extracrevicular method was performed in 30 subjects selected randomly and categorized into three groups. Group I (Healthy, n=10), group II (Chronic periodontitis, n=20) and group III (After treatment group, n=20). Scaling and root planing (SRP) was performed and GCF was collected after 8 weeks of treatment. MMP-3 levels were estimated in GCF samples using enzyme linked immunosorbent assay (ELISA). Results: MMP-3 was detected in all samples. Highest mean MMP-3 concentrations in GCF were obtained for group II (7.490 ng/ml), while the lowest concentrations were seen in group I (0.344 ng/ml) and group III (2.129 ng/ml). This suggests that MMP-3 levels in GCF increases proportionally with the progression of periodontal disease and decreases after treatment. Conclusion: There is a substantial increase in the concentrations of MMP-3 as periodontal disease progresses. Since MMP-3 levels in GCF are positively correlated with gingival index, probing pocket depth and clinical attachment level, MMP-3 may be considered as a "novel biomarker" in periodontal disease progression. However, controlled, longitudinal studies are needed to confirm this possibility.